ANTHELMINTIC ACTIVITY OF Cuminum cyminum, FOENICULUM VULGARE AND Eugenia caryophyllusAGAINST Pheritima posthuma - Satish Kumar; Kamal Kumar Goyal; Syed Bilal (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2012)
Ethanol extract of fruit of Cuminum cyminum (EECC), aqueous extract of fruit of Cuminum cyminum (AECC), Ethanol extract of fruit of Foeniculum vulgare (EEFV), aqueous extract of fruit of Foeniculum vulgare (AEFV) and Ethanol extract of flowering bud of Eugenia caryophyllus( EEEC), aqueous extract of flowering bud of Eugenia caryophyllus( AEEC) were taken up for in vitro studies on the Anthelmintic activity against Pheritima posthuma. Different concentrations (25, 50, 100, 200mg/mL) were used for the activity is compared with the reference standard Albendazole at concentration 20mg/mL and normal saline( 0.9% NaCl) was used in control treatment. The results were expressed in terms of time in minutes to report the time of paralysis and time of death of the earth worms. The results obtained from study indicate towards anthelmintic activity, supporting folk used of all three plants compared with reference standard. The result established that EEEC and AEEC is more potent as compared with EECC, AECC and EEFV, AEFV.Key words: Anthelmintic activity, Cuminum cyminum, Eugenia caryophyllus, Foeniculum vulgare, Pheritima posthuma.